The Complex Interplay of Factors and Strategies on Second Language Acquisition - Muh. Hasrun Fitriady; Riska Alifiah Zalsabila; Ramlah Ramlah; Lia Maisyaratul Hayah (Journal of Language Learning and Assessment, 2025)
Purpose This research paper aims to investigate the methods learners use to acquire second languages and the factors that affect Second Language Acquisition (SLA). Methodology The study collected data from two participants via semi-structured interviews: one via Zoom and the other face-to-face. Results/Findings The study found that SLA results from a combination of personal factors and environmental factors, which include age of acquisition, motivation, attitude, self-confidence, and anxiety, along with the teacher's role, technology use, social environment, and family support. Students utilized cognitive, metacognitive, social, and affective learning approaches that proved successful and appeared unique to them. Implication Research indicates that second language acquisition involves a complex and individualized process that demands contextually appropriate instruction along with emotional and social and technological assistance.